The relationship between global positioning system variables and injury occurrences in female field hockey - Choi, H.; Kim, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The noncontact and soft-tissue injuries to lower extremities that occur as a result of excessive running loads are largely preventable. This study investigated the relationship between global positioning system variables and noncontact soft-tissue injuries in female field hockey players based on their position on the field. Fifty-two players enrolled in the Korea National Team were monitored using global positioning system units in game-based training and competitions. The measurements obtained were total distance covered, high-intensity running distance, work-rest ratio, meters per minute, repeated high-intensity effort bouts, maximal velocity, and acceleration and deceleration bouts. Noncontact soft-tissue injuries in lower extremities were documented throughout the same period. For measuring the absolute external workload of each global positioning system variable, players` data were averaged for 1- and 4-week periods before they were injured (injury-related block), averaging values across 1 and 4 weeks before the injury-related block (non-injury block), as well as averaging values from the beginning of the data collection to the point of injury (total average). These blocks were compared to each other and to the corresponding total averages for the 1- and 4-week periods, depending on their position on the field. Of the 52 players, 28 players (8 forwards, 11 midfielders, and 9 defenders) injured their lower extremities for a total of 38 injuries. Of these injuries, 11 occurred in forwards, 17 occurred in midfielders, and 10 occurred in defenders with some players experiencing more than one injury. Different positions on the field have different global positioning system variables related to the occurrence of noncontact soft-tissue injuries in lower extremities, but there was a significant difference in global positioning system variable of injury-related block for only the 4-week period among their position on the field. Especially, increases in high-intensity running distance and repeated high-intensity effort bouts of defenders during the 4-week period were significantly related to the occurrence of injuries. To decrease the risk of injury in female field hockey players, different global positioning system variables should be monitored and modified in planned future training or competitions.